The Dynamics of Family Law Reform in Muslim Societies: A Comparative Fiqh Analysis of Gender Justice and Legal Modernization - Husain Husain; Achmad Lubabul Chadziq; Fitri Sari Setyorini; Nur Faizah; Siti Khadijah Abdullah Sanek (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study examines the dynamics of family law reform in Muslim societies through a comparative fiqh perspective, with a particular focus on gender justice and legal modernization. The research is motivated by the growing tension between classical Islamic legal doctrines and contemporary demands for equality, especially in the domain of family law, which directly governs gender relations. It aims to analyze how Muslim countries reinterpret Islamic legal principles to accommodate evolving social realities while maintaining normative legitimacy. This research employs a qualitative legal method with a comparative and normative approach. Primary data consist of statutory regulations on family law from selected Muslim-majority countries, including Indonesia, Morocco, and Tunisia, while secondary data are derived from classical fiqh literature, contemporary scholarly works, and international human rights instruments. Data are collected through document analysis and examined using interpretative and comparative analytical techniques grounded in maqāṣid al-sharī‘ah. The findings reveal that reforms in family law across Muslim societies demonstrate a shift from rigid textualism toward contextual and purposive interpretations of Islamic law. Countries adopting progressive reforms tend to integrate gender justice principles by reinterpreting doctrines such as qiwāmah, polygamy, and divorce rights, aligning them with broader objectives of justice, welfare, and human dignity. Moreover, the incorporation of international human rights norms has influenced legal restructuring, although often mediated by local religious and political considerations. In conclusion, the study affirms that the integration of gender justice within Islamic family law is both normatively justifiable and socially necessary, and therefore recommends the adoption of a maqāṣid-based interpretative framework alongside institutional legal reform to ensure a more equitable, adaptive, and sustainable family law system in Muslim societies.